2017
DOI: 10.1155/2017/3520967
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Measurement of Paper Basis Weight Using Phase Shift in Terahertz Time-Domain Spectroscopy

Abstract: THz time-domain spectroscopy has evolved as a noncontact, safe, and efficient technique for paper characterization. Our previous work adopted peak amplitude and delay time as features to determine paper basis weight using terahertz time-domain spectroscopy. However, peak amplitude and delay time tend to suffer from noises, resulting in degradation of accuracy and robustness. This paper proposes a noise-robust phase-shift based method to enhance measurements of paper basis weight. Based on Fresnel Formulae, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Furthermore, phase shift, which has been verified to be associated with sample thickness, can be deduced from phase spectra of sample signal and reference signal [46]. As can be seen from Fig.5 (a) and (b), although there were some differences in amplitude and phase spectrums between the four samples, it was hard to get directly the relationship between the amplitudes spectrums and coating thicknesses of the multilayered structures.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, phase shift, which has been verified to be associated with sample thickness, can be deduced from phase spectra of sample signal and reference signal [46]. As can be seen from Fig.5 (a) and (b), although there were some differences in amplitude and phase spectrums between the four samples, it was hard to get directly the relationship between the amplitudes spectrums and coating thicknesses of the multilayered structures.…”
Section: Methodsmentioning
confidence: 98%
“…The signal had been normalized to the maximum reference signal. Usually, THz signal feature in frequency domain was extracted to help characterizing materials, such as single layer coatings [12] and paper basis weight [46]. Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, the multi-resolution statistical analysis method combining wavelet transform and principal component analysis (PCA) was presented improving the information of thermal image to distinguish defects, and the detectability of damage caused by different impact energy was discussed [3]. Fan et al proposed a noise-robust phase-shift based method to enhance measurements of paper basis weight, the result shows that is superior to the others [4]. Wang et al used advanced thermal image algorithms processing thermal data obtained by three different thermographic methods, they found that principal component analysis applied to long pulse thermography provides accurate imaging results over traditional pulsed thermography and step heating thermography [5].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research is being carried out into the development of affordable and adaptable sensing gadgets [1][2][3][4][5]. Owing to their minimalism, affordability, and the rapidity with which they can be manufactured, paper sensors have been garnering more attention [6][7][8][9]. For instance, Gandhiraman et al are working on scalable and inexpensive single-use paper sensors for use in the field of DNA detection on the basis of chemical vapor deposition [9].…”
Section: Introductionmentioning
confidence: 99%